The Impact of Islamic Counseling Intervention towards Students’ Mindfulness and Anxiety during the COVID-19 Pandemic: Array - Asroful Kadafi; Alfaiz Alfaiz; M. Ramli; Dahlia Novarianing Asri; Juwita Finayanti (Islamic Guidance and Counseling Journal, 2021)
The pandemic caused by the Corona Virus Disease (COVID-19) has had psychological and health impacts on people's lives around the world. On a psychological aspect, this pandemic has caused anxiety due to low mindfulness. To increase the potential of mindfulness, one of the ways taken is by counselor psychological intervention. The authors used an Islamic counseling approach to reduce anxiety and increase mindfulness. Therefore, the research was conducted using a quasi-experimental design with non-equivalent control group design. Participants in this study were 14 students consisting of 7 students for each experimental and control group. Participants were invited after filling self-report the anxiety scale facing COVID-19 and indicated that they were in the high category. The data analyzed with the Wilcoxon sign rank test to determine the impact of before and after the intervention was given, then used the Mann Whitney to find out the mean differences between the experimental and control group, and the Rank Spearman to determine the correlation between mindfulness and anxiety. The results showed that Islamic counseling intervention is effective to increase mindfulness which impacted on reducing anxiety in facing the COVID-19 pandemic. Besides, the results of correlation analysis using the Rank Spearman show that there is a correlation between mindfulness and anxiety.